Kinerja Keuangan dan Nilai Perusahaan : Analisis Data Panel pada Jakarta Islamic Index - Yudhistira Ardana (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2018)
His study aims to determine the effect of financial performance on the value of the company. Data collection is conducted in 2012 until 2017. This research tries to analyze the influence of financial performance proxy with 3 (three) free variable, that is ratio of liquidity (quick ratio) as X1, profitability ratio (ROA) as X2, and solvency ratio (Debt to Total Assets Ratio) as X3 against the dependent variable / bound in the form of company value (Price Book Value) as Y at the company registered in Jakarta Islamic Index (JII). Data analysis technique used in this research is using panel data regression. The results of this study are independent variables profitability and solvency ratios have a positive and significant effect on the dependent variable in the form of company value measured by Price to Book Value (PBV). While the independent variable liquidity ratio measured by quick ratio has no effect on the value of the company.